Exploring strategies to control the cost of food security: Evidence from Bangladesh. (February 2022) - Jalilov, Shokhrukh-Mirzo; Rahman, Wakilur; Palash, Salauddin; Jahan, Hasneen; Mainuddin, Mohammed; Ward, Frank A.
Abstract: CONTEXT: A classical challenge in the search for principles and guidelines to protect food security affordably in the developing world comes from the well-known dilemma faced by farmers who incur economic losses from low prices brought on by excess production combined with poorly developed policies to anticipate, adapt to, and manage production and price fluctuations. This challenge is elevated in the face of growing evidence of climate change. OBJECTIVE: This work performs a series of policy experiments to discover an affordable set of measures to protect food grain security as well as assure profitability of high valued crops in Bangladesh. METHODS: This work uses primary and secondary data from Bangladesh agriculture to develop an empirical mathematical programming economic optimization model to achieve each of four alternative food policy objectives. RESULTS AND CONCLUSIONS: Results show total economic welfare achievable under each policy objectives: protecting baseline observed farm sector outcomes, minimum protection of food grain security, protection of farm income from producing high value crops, and unconstrained food welfare optimization. The application is to an important farming region of northwest Bangladesh. We find that policymakers can achieve both food grain security and farm income from high value crops at a minimum cost of economic welfare displaced. SIGNIFICANCE: The use of empirical models that describe and predict farm economic optimization behavior can provide guidance in the search for affordable policies for protecting food grain security while protecting farm income in the developing world. Graphical abstract: Unlabelled Image Highlights: We address a classical challenge in the search for principles and guidelines to protect food security affordably This study conducts four policy experiments to assess food security in Bangladesh. We find that policymakers can achieve both food grain security and profitable production of high value crops.